Fetus in Fetu as a suprarenal mass in a neonate - a rare and perplexing entity - Namratha Ravishankar; Sheeladevi CS; Joxce Pazhayattil (University of São Paulo, 2022)
Fetus in fetu (FIF) is a rare entity in which a malformed vertebrate fetus is incorporated within its twin. This entity should be differentiated from a teratoma, which has more malignant potential. We describe a neonate with a heterogeneous calcified suprarenal mass. The aspiration cytology revealed a heterogeneous cell population with spindle cells and small round blue cells. Operative and histopathologic examination showed features consistent with a fetus in fetu. This case report describes a rare entity and discusses its clinical presentation, cytological features on fine-needle aspiration, and the difficulties posed in its differentiation from a teratoma.